Forms of Liability of Minimarket Businesses for the Transfer of Money Back: Bentuk Pertanggungjawaban Pelaku Usaha Minimarket atas Pengalihan Uang Kembalian - Ilman, Mohamad Yazid; Mediawati, Noor Fatimah (Indonesian Journal of Law and Economics Review, 2021)
Donation, is one of the activities that has become a trend lately, many organizations and even individuals are competing in making donations. As is the case, what is done by minimarkets that carry out donation activities from the rest of the consumer's change. On this basis, a study entitled "Forms of Accountability of Minimarket Business Actors for the Transfer of Change" is carried out is one of the studies that aims to determine the form of accountability of business actors who carry out the act of transferring consumer change into the form of donations. Also, to analyze transaction engagements carried out by Consumers with business actors who take action to transfer Consumers' change in the form of donations. The research method that the author uses is a normative research method that uses a search for basic legal materials to make a legal decision on the legal case being studied. This study uses a statue approach and primary data which contains laws and regulations related to the legal issues under study. The results of the research, in this research, the activity of transferring the buyer's change into a legal donation is carried out if the buyer agrees to anything without any coercion or discrimination that harms the consumer. In addition, this study explores the law of engagement which regulates the engagement between consumers and transaction activities carried out by business actors. The engagement is considered valid if the transaction is carried out without any elements of coercion, fraud, extortion and discrimination.